Efecto de tres biorreguladores en el cultivo de pimiento capsicum annuum l en la granja Santa Inés - Luna Romero, Angel Eduardo (2013)
Farm "St. Agnes", Technical University of Machala, parish Change was held fieldwork where we studied the effects of using three Bioregulators organic growth in the cultivation of pepper, the same that were planted objectives: (1) To determine the response of pepper (Capsicum annuum L.) to three bio-applications, Miros, Agrostemin prolific and experimental farm in St. Agnes. (2) Conduct analysis of production cost per treatment. Irazu Long pepper (Capsicum annuum L.) was used in the test area of 916.50 m². The seed was germinating trays and transplanted at 15 days after germination, using the design of randomized complete block, with a witness and has three treatments, arranged in five blocks, giving 20 experimental units. The treatments used were: Prolific, Agrostemin and Miros. The variables studied were: plant height at 30 and 60 days to harvest, days to flowering and harvest, weight, length, fruit diameter, number of fruits per plant and per hectare, and the quality of these (first, second and rejection). Prolific products, Agrostemin and Miros, physiological activity enhanced the process of reserve accumulation in the fruits, thus increasing the length, diameter and weight of their fruit, showing statistically significant relative to the control, being treated like the Miros that manages to increase the production of first class on a 234.74%, similarly the Profilic and Agrostemin with 123.57% 154.23% and the respective manner on the production of first class fruits achieved by the witness . The yield was in the order of Miros, Agrostemin, Profilic and the witness had a negative return.